Efficacy of different substrates to formulate Trichoderma harzianum against seedling disease of cabbage - Faruk, MI (Bangladesh Journal of Agricultural Research, 2019)
Efficacy of three different substrates viz. rice bran, wheat bran, grass pea bran and their combination along with or without Mustard oilcake (MOC) were tested to formulate Trichoderma harzianum based bio-fungicides for the management of seedling disease (Fusarium oxysporum) of cabbage in seedbed. All combinations of substrates were equally suitable for mass culturing and preparing of T. harzianum bio-fungicides and all the substrates based T. harzianum bio-fungicides were effective in increasing seedling emergence and reducing pre-emergence and post-emergence mortality of cabbage seedling under F. oxysporum inoculated seedbed soils. The shoot length, shoot weight, root length and root weight of cabbage seedling were enhanced significantly by the application of different substrates based T. harzianum bio-fungicides under F. oxysporum inoculated soil under seedbed conditions. The individual (rice bran, wheat bran, grasspea bran) and combination of substrates (rice bran + wheat bran, rice bran + grasspea bran, rice bran + Mustard oilcake, rice bran + wheat bran + MOC and wheat bran + grass pea bran + MOC) were equally suitable to formulate effective T. harzianum based bio-fungicides for the management of foot and root rot disease of cabbage seedling in seed bed condition. Bangladesh J. Agril. Res. 44(1): 127-138, March 2019